Composition and structure of the fauna of ground beetles (Coleoptera, Carabidae) of the Zerafshan Range - Fazlitdin Khalimov (Acta Biologica Sibirica, 2023)
The article presents the results of studying the fauna of ground beetles in the western part of the Zerafshan Range (Uzbekistan). The Carabidae list includes 81 species from 41 genera, 18 tribes and nine subfamilies. The ecological diversity of the ground beetle fauna is analyzed on three parts of the ridge. The greatest diversity of Carabidae is noted in the Karatepo Mountains (74 species), and the smallest in the Zirabulak-Ziyadin Mountains (54 species). The fauna of the ground beetles of the Chakalikalyan and Karatepa Mountains are closer to each other (Jaccard index – 0.79, Chekanovsky-Sørensen coefficient – 0.89). The lowest value of the similarity coefficients was noted between the Chakalikalyan and Zirabulak-Ziadin Mountains (0.64; 0.78). The most numerous are Anchomenus dorsalis (10.46%), Calathus ambiguus (8.23%), Amara aenea (7.48%) and Harpalus rufipes (6.03%).